Conformational flexibility of the oncogenic protein LMO2 primes the formation of the multi-protein transcription complex - Sewell, H; Tanaka, T; El Omari, K; Mancini, E; Cruz, A; Fernandez-Fuentes, N; Chambers, J; Rabbitts, T (Springer Nature, 2014)
LMO2 was discovered via chromosomal translocations in T-cell leukaemia and shown normally to be essential for haematopoiesis. LMO2 is made up of two LIM only domains (thus it is a LIM-only protein) and forms a bridge in a multi-protein complex. We have studied the mechanism of formation of this complex using a single domain antibody fragment that inhibits LMO2 by sequestering it in a non-functional form. The crystal structure of LMO2 with this antibody fragment has been solved revealing a conformational difference in the positioning and angle between the two LIM domains compared with its normal binding. This contortion occurs by bending at a central helical region of LMO2. This is a unique mechanism for inhibiting an intracellular protein function and the structural contusion implies a model in which newly synthesized, intrinsically disordered LMO2 binds to a partner protein nucleating further interactions and suggests approaches for therapeutic targeting of LMO2.